Improved catalytic activity of PrMO3 (M = Co and Fe) perovskites: synthesis of thermally stable nanoparticles by a novel hydrothermal method. (2nd March 2015) - Megarajan, Suresh Kumar; Rayalu, Sadhana; Nishibori, Maiko; Labhsetwar, Nitin
<x xml:space="preserve">Abstract</x> A simple hydrothermal method was used to synthesize nanoperovskites using metal cyano complexes as precursors.